Experimental Investigation on Influence of Acidic Dry-Wet Cycles on Karst Limestone Deterioration and Damage - Yan Zhang; Zicheng Wang; Guoshao Su; Zhekang Wu; Fengtao Liu (Geofluids)
This study is aimed at the problem of limestone deterioration and damage caused by the combination of acid rain and the dry-wet cycle in Guilin. Samples of limestone were taken to study the influence of acidic dry-wet cycles on limestone deterioration and damage. This was accomplished by performing nuclear magnetic resonance (NMR) measurements and inductively coupled plasma atomic emission spectrometer measurements on the limestone samples. The study found that with an increase in the number of cycles, the T2 curve of the rock continuously shifts to the right, but the range of movement still decreases with pH increasing values. The T2 spectrum area, rock porosity, porosity deterioration, mass loss rate, and water absorption rate all increase with an increase in the number of cycles, but the growth rate continues to decrease, and the increase is negatively correlated with pH. After the dry-wet cycles, the mass concentration of each element in the beaker is Ca, Mg, and Fe in order from high to low, and the mass concentration of each main element in the reaction solution increases with the increase in the number of acidic dry-wet cycles.